BENTUK LIRIK LAGU ANAK DI TAMAN KANAK-KANAK JAKARTA TIMUR:KAJIAN INTERTEKSTUAL - Anggraeni, Putri; Hidayatullah, Syarif (Universitas Hamzanwadi, 2022)
Children's song lyrics in kindergarten always have their own characteristics. Children's song lyrics found in kindergarten are usually song lyrics adapted from previous song lyrics. Children's song lyrics are taught in kindergarten to train children or teach children various things such as religious values, independence, introduction to animals and others. The purpose of this study was to describe the form of the lyrics of children's songs sung in Kindergarten based on the types of hypograms. The subjects in this study were the lyrics of children's songs at the Kindergarten PG/RA Al Bakiriyah East Jakarta, TK Laboratory Jakarta, and PAUD Harapan Mulya. This research is a qualitative research with content analysis technique. The content analysis technique of this research is by collecting data and describing it by collecting data, presenting data, and conclusions. The result of this research is that there are 14 songs from 3 kindergartens in Jakarta. 1 song is included in the expansion hypogram, there are 7 songs included in the convention hypogram, there are 6 songs included in the hypogram, and none of the songs are included in the Ekserp hypogram.Keywords: Intertextual, Children's Song Lyrics, Hypograms